2015
DOI: 10.4141/cjss-2014-038
|View full text |Cite
|
Sign up to set email alerts
|

Depth to compact subsoil effects on soil properties and barley–potato yields on a loamy soil in New Brunswick

Abstract: . Depth to compact subsoil effects on soil properties and barley Á potato yields on a loamy soil in New Brunswick. Can. J. Soil Sci. 95: 203Á218. An experiment was established to investigate the implications of thickness of soil over compact subsoil on plow layer soil thermal and water regimes and ultimately the yield of potato (Solanum tuberosum L.) and barley (Hordeum vulgare L.). Three depths were considered, 24 cm (shallow), 36 cm (medium) and 60 cm (deep). Results on soil temperature impacts were inconclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…For example, whereas PC1 may reflect the response of tuber yield to spatial variation in soil texture and organic matter, the PC3 may reflect where there is a more pronounced effect of concave or convex landforms on tuber yield through soil water availability (drought or excess) or through soil depth (erosion or deposition). For example, there is evidence that tuber yield in New Brunswick is commonly limited by water availability (Bélanger et al, 2000) and by soil depth (Rees et al, 2015). This is consistent with the opposing direction of the vectors for slope curvature with silt and SOC in a biplot of PC1 vs. PC3 (Figure 3).…”
Section: Pcasupporting
confidence: 57%
“…For example, whereas PC1 may reflect the response of tuber yield to spatial variation in soil texture and organic matter, the PC3 may reflect where there is a more pronounced effect of concave or convex landforms on tuber yield through soil water availability (drought or excess) or through soil depth (erosion or deposition). For example, there is evidence that tuber yield in New Brunswick is commonly limited by water availability (Bélanger et al, 2000) and by soil depth (Rees et al, 2015). This is consistent with the opposing direction of the vectors for slope curvature with silt and SOC in a biplot of PC1 vs. PC3 (Figure 3).…”
Section: Pcasupporting
confidence: 57%
“…However, the depth of compaction and water stress differs in deep-and shallow-rooted crops (Saini & Chow, 1982). For example, Rees et al (2015) evaluated the effect of compacted subsoil layers at three depths (10, 14 and 24 inches) on soil properties and yields of potato and barley (Hordeum vulgare L.) (i.e., shallow-and deep-rooted crops, respectively) in a loamy soil. For potato, they observed that yields averaged across 3 yr did not differ among the compacted layer depths, whereas barley yields significantly increased with the depth of the compaction layer.…”
Section: Ta B L E a Useful Conversionsmentioning
confidence: 99%
“…As more limiting factors are relieved, nutrient use efficiency must increase. In the case of potato crops, irrigation scheduling (Haverkort and Struik, 2015), remedial measures against soil compaction (Stalham et al, 2005;Rees et al, 2015) and crop sequences could improve nutrient use efficiency.…”
Section: Selection Of the Response Functionmentioning
confidence: 99%